Colonocyte keratin 7 is expressed de novo in inflammatory bowel diseases and associated with pathological changes and drug-resistance - Polari Lauri; Tenhami Mervi; Anttila Santeri; Helenius Terhi; Kujari Harry; Kallajoki Markku; Voutilainen Markku; Toivola Diana M. (Nature Research, 2025)
The clinical course of IBD, characterized by relapses and remissions, is difficult to predict. Initial diagnosis can be challenging, and novel disease markers are needed. Keratin 7 (K7) is a cytoskeletal intermediate filament protein not expressed in the colonic epithelium but has been reported in IBD-associated colorectal tumors. Our aim was to analyze whether K7 is expressed in chronic colonic inflammatory diseases and evaluate its potential as a novel biomarker. K7 was analyzed in two patient cohorts using immunohistochemistry-stained colon samples and single-cell quantitative digital pathology methods. K7 was correlated to pathological changes and clinical patient characteristics. Our data shows that K7 is expressed de novo in the colonic epithelium of ulcerative colitis and Crohn’s disease IBD patients, but not in collagenous or lymphocytic colitis. K7 mRNA expression was significantly increased in colons of IBD patients compared to controls when assessed in publicly available datasets. While K7 increased in areas with inflammatory activity, it was not expressed in specific crypt compartments and did not correlate with neutrophils or stool calprotectin. K7 was increased in areas proximal to pathological alterations and was most pronounced in drug-resistant ulcerative colitis. In conclusion, colonic epithelial K7 is neo-expressed selectively in IBD patients and could be investigated for its potential as a disease biomarker.